Chemotherapy-elicited exosomal miR-378a-3p and miR-378d promote breast cancer stemness and chemoresistance via the activation of EZH2/STAT3 signaling - Yang, Qianxi (J Exp Clin Cancer Res, 2021)
BACKGROUND: Not all breast cancer (BC) patients who receive neoadjuvant chemotherapy achieve a pathologic complete response (pCR), but the reasons for this are unknown. Previous studies have shown that exosomes produced in the tumor microenvironment in response to chemotherapy promote a chemotherapy-resistant phenotype in tumors. However, the role of BC chemotherapy-elicited exosomes in regulating chemoresistance is poorly understood. METHODS: Using commercial kits, serum exosomes were extracted from patients before neoadjuvant chemotherapy, after one cycle of chemotherapy and after four cycles of chemotherapy consisting of doxorubicin (DOX) and paclitaxel (PTX). Their miRNAs were sequenced, and the correlation between the sequencing results and chemotherapy effects was further verified by RT-qPCR using patient serum exosomes. Cell Counting Kit-8 (CCK-8) was used to detect chemosensitivity. Stemness was assessed by CD44+/CD24- population analysis and mammosphere formation assays. Chromatin immunoprecipitation (ChIP) experiments were performed to verify the binding of signal transducer and activator of transcription 3 (STAT3) to the promoter of miRNAs. RESULTS: Here, we provide clinical evidence that chemotherapy-elicited exosomal miR-378a-3p and miR-378d are closely related to the chemotherapy response and that exosomes produced by BC cells after stimulation with DOX or PTX deliver miR-378a-3p and miR-378d to neighboring cells to activate WNT and NOTCH stemness pathways and induce drug resistance by targeting Dickkopf 3 (DKK3) and NUMB. In addition, STAT3, which is enhanced by zeste homolog 2 (EZH2), bound to the promoter regions of miR-378a-3p and miR-378d, thereby increasing their expression in exosomes. More importantly, chemotherapeutic agents combined with the EZH2 inhibitor tazemetostat reversed chemotherapy-elicited exosome-induced drug resistance in a nude mouse tumor xenograft model. CONCLUSION: This study revealed a novel mechanism of acquired chemoresistance whereby chemotherapy activates the EZH2/STAT3 axis in BC cells, which then secrete chemotherapy-elicited exosomes enriched in miR-378a-3p and miR-378d. These exosomes are absorbed by chemotherapy-surviving BC cells, leading to activation of the WNT and NOTCH stem cell pathways via the targeting of DKK3 and NUMB and subsequently resulting in drug resistance. Therefore, blocking this adaptive mechanism during chemotherapy may reduce the development of chemotherapy resistance and maximize the therapeutic effect. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13046-021-01901-1.